2014
DOI: 10.1002/jcph.398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hepatic impairment on lenvatinib pharmacokinetics following single‐dose oral administration

Abstract: This open-label, single-dose study assessed lenvatinib pharmacokinetics (PK) in subjects with normal hepatic function (n ¼ 8) and mild, moderate, or severe hepatic impairment (n ¼ 6 each). Subjects received 10 mg oral lenvatinib, except those with severe hepatic impairment (5 mg). Plasma and urine samples were collected over 14 days; free and total lenvatinib and its metabolites were analyzed using validated chromatography/spectrometry. PK parameters were estimated using noncompartmental analysis. There were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 27 publications
0
36
0
1
Order By: Relevance
“…After administration of a single dose, the C max of 12 mg lenvatinib in the CP-A group was similar to that in patients with solid tumors who received a 12 mg dose, but lower than in those who received 25 mg. However, since lenvatinib oral clearance after administration of multiple doses in patients with HCC was decreased in this study, the C 24 h of 12 mg in the CP-A group was higher than that in patients with solid tumors who received 12 mg lenvatinib, and was comparable to that of those who received 25 mg. Shumaker and colleagues (31) showed that lenvatinib AUCs and oral clearance were similar for single-dose administration between healthy subjects and those with mild (CP-A) or moderate (CP-B) hepatic impairment. The reason for the discrepancy in PK outcomes related to hepatic impairment between subjects without HCC and patients with HCC is unknown, but may result from differences in underlying hepatic etiology (32).…”
Section: Discussionmentioning
confidence: 98%
“…After administration of a single dose, the C max of 12 mg lenvatinib in the CP-A group was similar to that in patients with solid tumors who received a 12 mg dose, but lower than in those who received 25 mg. However, since lenvatinib oral clearance after administration of multiple doses in patients with HCC was decreased in this study, the C 24 h of 12 mg in the CP-A group was higher than that in patients with solid tumors who received 12 mg lenvatinib, and was comparable to that of those who received 25 mg. Shumaker and colleagues (31) showed that lenvatinib AUCs and oral clearance were similar for single-dose administration between healthy subjects and those with mild (CP-A) or moderate (CP-B) hepatic impairment. The reason for the discrepancy in PK outcomes related to hepatic impairment between subjects without HCC and patients with HCC is unknown, but may result from differences in underlying hepatic etiology (32).…”
Section: Discussionmentioning
confidence: 98%
“…The influence of body weight on the pharmacodynamics of antiangiogenic agents and resultant toxicity patterns is still uncertain [26]. Additionally, increased lenvatinib exposure was found in patients with severe hepatic impairment [27]. It is possible that in patients with HCC, who typically have impaired hepatic function, lenvatinib PK is more affected by body weight than in healthy individuals or patients with other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This mass balance study therefore warrants to further examine the effect of renal and hepatic impairment on the pharmacokinetics of lenvatinib, and clinical trials to investigate this have been performed. The results of a hepatic impairment trial were recently published by Shumaker et al and led to the conclusion that a reduced dose is advisable for subjects with severe hepatic impairment [17].…”
Section: Discussionmentioning
confidence: 99%